The Effectiveness of Logotherapy in Enhancing Meaning in Life Among Individuals with Depressive Disorders: A Systematic Literature Review - Dhiya’ Almirra Azzahra; M. Suharsono (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Depressive disorder is a mental health condition commonly characterized by feelings of emptiness, loss of interest, decreased energy, and reduced motivation, reflecting a crisis of life meaning. Depression, beyond affective and somatic symptoms, is intrinsically associated with feelings of emptiness and a loss of life purpose. Logotherapy, developed by Viktor Frankl, emphasizes the search for meaning in life, known as the will to meaning, as the primary motivational force in humans, and posits that suffering can be transformed when individuals find meaning within it. The research method used a systematic literature review with reference to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature search was conducted through Google Scholar, PubMed, and Crossref databases using the keywords "logotherapy," "meaning in life," and "depression." The selected articles were national and international publications published between 2020-2025, available in full text, and involving individuals with depressive disorders. A total of 7 articles met the inclusion criteria and were analyzed qualitatively. Observational results indicate that logotherapy is consistently effective in increasing the sense of meaning in life and reducing depressive symptoms in various populations. This effectiveness is mediated through increasing purpose in life, strengthening adaptive attitudes toward suffering, reducing negative thoughts, and increasing hope and personal responsibility. Thus, logotherapy can be considered an effective and relevant meaning-based psychological intervention, both as primary therapy and complementary therapy in the treatment of depressive disorders.Gangguan depresi merupakan masalah kesehatan mental yang tidak hanya ditandai oleh gejala afektif dan somatik, tetapi juga oleh perasaan hampa, kehilangan tujuan hidup, dan krisis eksistensial. Kondisi ini menunjukkan adanya keterkaitan yang kuat antara depresi dan hilangnya kebermaknaan hidup. Logoterapi, yang dikembangkan oleh Viktor E. Frankl, menekankan pencarian makna hidup (will to meaning) sebagai motivasi fundamental manusia dan memandang bahwa penderitaan dapat ditransformasikan ketika individu mampu menemukan makna di dalamnya. Penelitian ini bertujuan untuk meninjau secara sistematis bukti-bukti empiris mengenai efektivitas logoterapi dalam meningkatkan kebermaknaan hidup pada penderita gangguan depresi. Metode penelitian menggunakan systematic literature review dengan mengacu pada pedoman Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Pencarian literatur dilakukan melalui database Google Scholar, PubMed, dan Crossref dengan menggunakan kata kunci “logotherapy”, “meaning in life”, dan “depression”. Artikel yang diseleksi merupakan publikasi nasional dan internasional yang diterbitkan dalam rentang tahun 2020–2025, tersedia dalam teks lengkap, dan melibatkan individu dengan gangguan depresi. Sebanyak 7 artikel memenuhi kriteria inklusi dan dianalisis secara kualitatif. Hasil tinjauan menunjukkan bahwa logoterapi secara konsisten efektif dalam meningkatkan kebermaknaan hidup dan menurunkan gejala depresi pada berbagai populasi. Efektivitas tersebut dimediasi oleh peningkatan tujuan hidup, penguatan sikap adaptif terhadap penderitaan, pengurangan pikiran negatif, serta peningkatan harapan dan tanggung jawab personal. Dengan demikian, logoterapi dapat dipertimbangkan sebagai intervensi psikologis berbasis makna yang efektif dan relevan, baik sebagai terapi utama maupun terapi komplementer dalam penanganan gangguan depresi.